Runoff prediction in ungauged basins : synthesis across processes, places and scales - Bloschl, Gunter, 1961- (Cambridge : Cambridge University Press, 2013)
'Predicting water runoff in ungauged water catchment areas is vital to practical applications such as the design of drainage infrastructure and flooding defences, runoff forecasting, and for catchment management tasks such as water allocation and climate impact analysis. This important new book synthesises decades of international research, forming a holistic approach to catchment hydrology and providing a one-stop resource for hydrologists in both developed and developing countries. Topics include data for runoff regionalisation, the prediction of runoff hydrographs, flow duration curves, flow paths and residence times, annual and seasonal runoff, and floods. Illustrated with many case studies and including a final chapter on recommendations for researchers and practitioners, this book is written by expert authors involved in the prestigious IAHS PUB initiative. It is a key resource for academic researchers and professionals in the fields of hydrology, hydrogeology, ecology, geography, soil science, and environmental and civil engineering'--
Includes bibliographical references (p. 415-462) and index.
Keywords: Runoff; Rain and rainfall; Runoff -- Mathematical models; Rain and rainfall -- Mathematical models; Hydrology